Subterranean structures and mycotrophy of the achlorophyllous Dictyostega orobanchoides (Burmanniaceae) - Imhof, Stephan (Universidad de Costa Rica, 2001)
Plants of Dictyostega orobanchoides arise from about 1 mm thick rhizomes, which are densely covered by sessile, imbricate, peltate scale leaves. The resulting interfoliar spaces are inhabited by fungal hyphae up to 6 μm thick, often developing vesicle-like bladders. The fungus also colonizes the tissue of the scale leaves, inter- as well as intracellularly, forming vesicles but no arbuscules, and it even penetrates the vascular bundles of the leaves. The rhizome itself does not become infected. The 200 μm thick roots emerge from the rhizome and have a 2-layered cortex and voluminous rhizodermis, which both are delicate and often disrupted or missing. In contrast, the strongly reinforced, tertiary endodermis and the central cylinder are durable and have a considerable tensile strength. Although the roots grow through the hyphal masses in the interfoliar spaces when emerging from the rhizome, they only become infected from the rhizosphere. A collar of rhizomogenous tissue hinders the interfoliar hyphae from direct contact to the roots. Only within the rhizodermis, the mycorrhizal fungus builds coils of heteromorphic hyphae, arbuscule-like structures, and vesicles. Hence, the mycorrhiza in D. orobanchoides is assigned to the arbuscular mycorrhiza. It is hypothezised, that the ephemeral mycorrhizal tissue combined with the durable vascular system of the roots is a strategy to avoid the high costs of protecting the large rhizodermal surface area. The rhizomogenous collar is explained as an extra protection to the tender, young roots, when emerging from the rhizome. The necessity to include other subterranean plant organs along with the roots in future mycorrhizal studies is emphasized.